Burn-In Aging Behavior and Analytical Modeling of Wavelength-Division Multiplexing Semiconductor Lasers: Is the Swift Burn-In Feasible for Long-Term Reliability Assurance?. (8th December 2013) - Huang, Jia-Sheng
Abstract : Effective and economical burn-in screening is important for technology development and manufacture of semiconductor lasers. We study the burn-in degradation behavior of wavelength-division multiplexing semiconductor lasers to determine the feasibility of short burn-in. The burn-in is characterized by the sublinear model and correlated with long-term reliability.